Acorn – weevil interactions in a mixed-oak forest: Outcomes for larval growth and plant recruitment - Muñoz, Alberto; Bonal, Raul; Espelta, Josep Maria (Forest Ecology and Management, 2014)
Weevils are the most important pre-dispersal acorn predators in the Mediterranean region, where oaks often form mixed forests and different weevil species can coexist. The performance of weevil larvae depends in great extent on their feeding activities inside the infested acorns that, in turn, are known to reduce the viability of acorns. In this paper, we have analysed the interactions among the weevil community and four oak species (Quercus pyrenaica, Quercus suber, Quercus faginea and Quercus ilex) coexisting in a Mediterranean mixed-oak forest. DNA sequencing of weevil larvae revealed four different weevil species (Curculio elephas, Curculio glandium, Curculio pellitus and Curculio venosus) infesting the acorns of the four oak species. Oak species differed in acorn size, and weevil species also differed in body size. Weevil species showed some degree of specificity among the four oak species, but specificity was not related to variations in acorn size. By contrast, larval development and seedling recruitment were mostly driven by inter-specific differences in larval and acorn size. Larger seeded species suffered less seed damages by weevils (i.e. embryo predation and cotyledon consumption), thus reducing the impacts of acorn infestation in seedling emergence and seedling size. Larval development for the largest weevil species C. elephas was constrained by cotyledon depletion in all acorn species. Yet, this pattern was not observed for other weevil species. Larval size of the same weevil species also varied among different oak species after controlling for the amount of cotyledon eaten by larvae, thus, variation of other acorn traits among acorn species (e.g. chemical composition) may also have consequences for the performance of weevil larvae. It is likely that other variables operating at population level, such as temporal and spatial changes in acorn production or phenological variations of weevils and oaks, are also implicated in the complex functioning of these outstanding mixed-oak forests where natural regeneration seems to be threatened.
Keywords: acorn; Host specificity; Larval development; Seedling recruitment; Weevil

Resource manipulation reveals flexible allocation rules to growth and reproduction in a Mediterranean evergreen oak - Pulido, Fernando; Moreno, Gerardo; Garcia, Eustolia; Obrador, Jose J; Bonal, Raul; Díaz, Mario (JOURNAL OF PLANT ECOLOGY, 2014)
Aims In plants, resource allocation to growth and reproduction may depart from trade-off expectations if (i) investment in growth and reproduction relies on different resource pools, (ii) allocation to reproduction is dependent upon reaching some growth threshold or (iii) reproduction is developmentally linked to growth, both functions relying on the same resource pool. We examined the effects of enhanced resource level on patterns of resource allocation to growth and reproduction in holm oak (Quercus ilex sbsp. ballota), a Mediterranean evergreen tree. Methods In the experimental year (2003), we manipulated the amount of soil nutrients in autumn (to increase nutrient uptake during shoot elongation in the following spring) and soil water in summer (to increase water uptake during acorn growth). Indicators of growth and male and female reproduction were estimated in the pre-experimental (2002), experimental (2003) and post-experimental (2004) years. Important Findings Fertilized trees produced significantly longer shoots, but the number of female flowers per shoot was not affected by treatments. The production of male catkins was also enhanced by fertilization. Irrigation did not affect the production of female flowers or abortion rates. Growth and female reproduction showed no consistent relationship in untreated trees, but resource addition elicited a growth-female reproduction trade-off in the experimental year. The sign of this significant relationship changed in the post-experimental year, indicating the existence of lagged effects of resource manipulation on acorn production. Overall, patterns of allocation to growth and reproduction varied as a function of sex, resource availability and year, a result consistent with extreme allocational plasticity in holm oak.
Keywords: acorn abortion; allocational plasticity; Dehesa; growth-reproduction trade-offs; nutrient addition; Quercus ilex; resource allocation

Seeding phenology influences wood mouse seed choices: the overlooked role of timing in the foraging decisions by seed-dispersing rodents - Sunyer, Pau; Espelta, Josep Maria; Bonal, Raul; Muñoz, Alberto (Behavioral Ecology and Sociobiology, 2014)
Scatter-hoarding rodents influence the population dynamics of plants by acting as seed predators and dispersers. Therefore, rodent foraging preferences for certain seed traits (species, size, condition) have been extensively studied. However, to what extent these preferences are fixed or they track the temporal changes on seed characteristics due to phenological differences has been seldom explored.We stud- ied the temporal variability in seed preferences by wood mouse (Apodemus sylvaticus), according to phenological changes in seed characteristics of two co-occurring oaks (Quercus ilex and Quercus pubescens). The phenology of acorn abundance and the acorn predation/dispersal patterns by rodents were monitored over an entire seeding season. Results revealed temporal changes in rodent preferences for acorns of the two oaks, matching their different seeding phe- nology (earlier in Q. pubescens and later in Q. ilex). On the other hand, whatever the species considered, rodents preferred larger and sound acorns along the entire season, although the dispersal of infested ones increased slightly during the peaks of acorn drop. The observed influence of seeding phenology on seed choices by rodents warns about inferring definite conclusions regarding their foraging behavior when arising from short-term experiments. Indeed, this study reveals that foraging preferences may be highly dynamic and context- dependent for some seed traits (e.g., species and condition), rather than fixed behavioral patterns. Plasticity in rodent for- aging choices may allowthem to successfully exploit different oaks with uncoupled seeding phenologies, while potentially favoring their coexistence.
Keywords: acorn; Apodemus sylvaticus; dispersal; Quercus; seed; seed traits

Positive cascade effects of forest fragmentation on acorn weevils mediated by seed size enlargement - Bonal, Raul; HERNÁNDEZ, MARISA; ORTEGO, JOAQUÍN; Muñoz, Alberto; ESPELTA, JOSEP M. (Insect Conservation and Diversity, 2012)
Abstract. 1. Today, forest fragmentation is one of the major threats to biodiversity worldwide. In this context, fragmented populations of specialised forest organisms face an increasing risk of extinction because of factors such as local food scarcity. Nonetheless, the role of food availability may differ depending on organism size, which is expected to determine the energy requirements and mobility between fragments. 2. A field study was carried out on Curculio elephas, a forest beetle with low dispersal potential, whose larval development takes place in oak Quercus spp. acorns. 3. For a similar seed crop per tree, acorn size was larger in isolated oaks than in trees located in forest patches. Thus, fragmentation increased local food availability for C. elephas. Larger acorns enabled larval size to increase, a key fitness proxy associated with individual survival, adult size, and potential female fecundity. Indeed, the number of both adults and larvae was higher in isolated trees than in forest patches. 4. In the current scenario of increasing forest fragmentation, the survival likelihood of specialist insects may strongly depend on their ability to adapt to altered environmental conditions. To the best of our knowledge, this is the first study to report on how some forest insects may take advantage of fragmentation-mediated changes to survive in isolated trees. 5. From a conservation perspective, management policies should preserve isolated trees as a source of seeds and fauna for the natural regeneration of forest ecosystems after unproductive farmlands have been abandoned.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn size; Curculio; Forest fragmentation; forest insects; Global change; individual fitness; larval size

Responses of a scatter-hoarding rodent to seed morphology: links between seed choices and seed variability - Muñoz, Alberto; Bonal, Raul; Espelta, Josep Maria (Animal Behaviour, 2012)
Seed preferences of scatter-hoarding granivores may inﬂuence the evolution of seed traits in plants. However, there is little evidence linking the granivores’ responses to speciﬁc seed traits to the variability of seeds in a single plant species. This information is essential for understanding how the decisions of granivores can shape plant life histories. We analysed how seed morphology (size and shape) of the Holm oak, Quercus ilex, inﬂuences seed choices of the seed-disperser, the Algerian mouse, Mus spretus. We studied the seed variability of the oak and whether the frequency of seed phenotypes matched the seed choices of the disperser. The probabilities of seed removal decreased as the seeds became larger and more bullet-shaped, so that seeds that were simultaneously large and bullet-shaped had the lowest probabilities of being dispersed. These seeds are probably refused by rodents because they impose higher handling and transport costs. The size and shape of the Holm oak seeds were highly variable between trees, but extraordinarily consistent within a single tree over different years. However, the analysis of seed variability revealed a disproportionately low frequency of large bullet-shaped phenotypes, which are those barely removed by rodents. Seed preferences of dispersers of species with high seed variability between trees can lead to differences in the chances of seeds produced by different trees being dispersed. Those seed phenotypes preferred by dispersers could make a higher contribution to the next generation, which could inﬂuence the evolution and variability of seeds in a plant species
Keywords: acorn; Algerian mouse; animal-plant interaction; handling cost; hoarding behaviour; Holm oak; Mus spretus; Quercus ilex; seed caching; small rodent

Complex selection on life-history traits and the maintenance of variation in exaggerated rostrum length in acorn weevils. - Bonal, Raul; Espelta, Josep Maria; Vogler, Alfried P. (Oecologia, 2011)
Trophic interactions can trigger the development of exaggerated specialized characters and promote morphological diversification. For example, acorn weevils (genus Curculio) present strikingly long rostrums, which are used by females to perforate oviposition holes through the seed coat. Species exhibiting longer rostrums are known to exploit larger acorns, and therefore rostrum length is thought to be subject to selection to match the preferred acorn type. However, rostrum length is strongly correlated with body size, and morphological divergence could result from either selection on rostrum length for optimal food exploitation or from other pressures acting on body size. We collected infested acorns at oak forests where the large Curculio elephas and the small-bodied Curculio glandium co-occur. There were no interspecific differences in adult female body size to rostrum length allometric relationships, and rostrum length is equally correlated with body size in either species. MtDNA-based species identification showed that C. glandium larvae were present within acorns of all sizes, whereas C. elephas larvae were restricted to acorns above a minimum size, irrespective of oak species. Hence, exploitation of large acorns can hardly have triggered rostrum enlargement, as the small sized C. glandium adults (with short rostrums) could perforate and oviposit in both small and large acorns. Rather, increased rostrum length is probably a by-product of the larger body sizes of individuals emerging from bigger acorns, which allow increased larval size and enhance larval survival likelihood. Summarizing, when exaggerated feeding traits co-vary with other body features, interspecific morphological variability may result from contrasting selective pressures acting on these correlated characters.
The following values have no corresponding Zotero field: accession-num: 21674207
Keywords: Body size; Curculio; Ecomorphological diversification; Quercus; Seed size; Trophic segregation

Linking seed dispersal to cache protection strategies. - Muñoz, Alberto; Bonal, Raul (Journal of Ecology, 2011)
The spatial distribution of dispersed seeds results from the combined action of the caching strategies followed by different granivores. Hence, it is essential to study the factors that influence seed predation and caching decisions to achieve a better understanding of the dispersal process. In this study, we document how seed dispersal and the spatial patterns of natural recruitment are linked to the strategies used by granivores to protect their cached seeds from pilferage. We present a theoretical model showing that those strategies may convey benefits for both seed cachers and plants. We studied the relationships among seed production, seed predation/caching, cache pilferage and plant recruitment in a savanna-like landscape of oaks dispersed by scatter-hoarding rodents. Our results show that acorn-dispersing rodents were concentrated under the canopies of scattered oaks, where the theft of cached acorns increased by 77% as compared to that of the surrounding open landscape. Acorns were thus cached selectively in the open areas to reduce pilferage; in fact, none of the few seeds cached beneath tree canopies survived predation by granivores (pilferage + recovery). Meanwhile, some acorns cached in the surrounding open areas were neither pilfered nor recovered and then recruited successfully. Accordingly, natural recruitment of newly emerged seedlings was higher outside than under canopies, suggesting that rodent caching strategies have direct implications for the directed dispersal of oaks. Synthesis. The spatial patterns of seed dispersal shape the fitness of both the plant because they influence dispersal and recruitment efficiency, and the granivores that cache and predate its seeds because they influence their foraging efficiency. Cache protection strategies reduce pilferage significantly and enhance seed recovery rates by the cache owner. At the same time, more seeds remain dispersed and unrecovered. Thus, cache protection strategies can provide net benefits to the plant in terms of effective directed dispersal. [ABSTRACT FROM AUTHOR]
Keywords: directed dispersal; granivores; plant recruitment; Quercus ilex; savanna-like landscapes; seed caching; seed predation; seedling emergence; small rodents

Mismatch between the timing of oviposition and the seasonal optimum. The stochastic phenology of Mediterranean acorn weevils - Bonal, Raul; Muñoz, Alberto; MARÍA ESPELTA, JOSEP (Ecological Entomology, 2010)
1. The timing of reproduction is predicted to match the period of maximum food availability. In this sense, the case of many phytophagous insects in temperate regions is very illustrative, as their larvae usually depend on a resource only available for a limited period of time each year. 2. For 3 years the interactions between the weevil Curculio elephas and the Mediterranean Holm oak Quercus ilex were studied. Weevil larvae grow within the acorns, feeding on the cotyledons. The timing of oviposition will determine food availability for the larvae, as acorns stop growing once they are attacked. 3. Acorn temporal growing patterns did not change between years and food availability for larvae was at its highest in October, when temperature was still suitable for larval development. However, oviposition phenology did change between years. In 2002 females oviposited later, larvae grew within larger acorns, and their body mass was significantly higher than in 2003 or 2004, when females oviposited into early acorns. 4. Thus, weevils do not always adjust oviposition to the best possible feeding conditions for their offspring. Rather, they seem to maximise their own lifetime fitness, ovipositing as soon as they emerge in late summer. Emergence, in turn, depends strongly on stochastic events such as summer storms in the Mediterranean region. 5. Under a climate change perspective, the trend towards higher August rainfall recorded in our study area may alter oviposition phenology, with the subsequent cascade effects on weevil body size and fitness
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; adult emergence; Curculio; oviposition; Phenology; stochastic events; Temperature; timing of reproduction

Pre-dispersal acorn predation in mixed oak forests: interspecific differences are driven by the interplay among seed phenology, seed size and predator size - ESPELTA, JOSEP M.; Bonal, Raul; Sánchez-Humanes, Belén (Journal of Ecology, 2009)
1. Pre-dispersal seed predation (PSP) often occurs in multi-host–predator systems (e.g. several plant species exposed to a common array of granivorous insects). However, whether the interaction among seed phenology, seed size and predator size accounts for interspecific differences in PSP remains elusive. 2. We studied PSP in a mixed-oak forest with two oaks (the larger-seeded Quercus humilis and the smaller-seeded Q. ilex), both depredated by two acorn weevils (the smaller Curculio glandium and the larger C. elephas). We intensively monitored acorn production and infestation phenology and we identified the weevil species depredating acorns by means of DNA taxonomy. 3. The minimum acorn size required for infestation was lower for C. glandium than for C. elephas, in accordance with their different body sizes. This resulted in an earlier infestation phenology in C. glandium and the ability of this species to infest both smaller and larger acorns. Above a minimum acorn size threshold, no selection for larger acorns by weevils was observed. 4. Initial acorn crop size was similar in the two oaks. Nonetheless, the earlier acorn phenology and the production of larger acorns in Q. humilis favoured the earlier infestation by C. glandium and the predation by both small and large weevils. Smaller acorns of Q. ilex almost excluded infestation by the larger C. elephas. 5. Although larger acorns of Q. humilis could better survive infestation (preserve the embryo), higher PSP in this species finally resulted in a lower mature acorn crop size than in Q. ilex. 6. Synthesis. In a multi-host–predator system, smaller-seeded species may benefit from a reduced PSP because they exclude larger granivorous insects, but also by means of a ‘free-rider effect’, if larger-seeded heterospecifics earlier reach a critical size to be depredated. These results also highlight the benefits of a small body size in granivorous insects to depredate seeds earlier and to forage on a wider range of seed sizes. Whether the advantage of ‘being small’ in this antagonistic plant–animal interaction is offset by other processes, or whether it results in a pressure towards seed and insect size reduction, deserves further attention.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Curculio elephas; Curculio glandium; Mediterranean oak forests; multi-host–predator system; Quercus humilis; Quercus ilex; seed ecology; seed satiation; species coexistence

Pre-dispersal acorn predation in mixed oak forests: interspecific differences are driven by the interplay among seed phenology, seed size and predator size - Espelta, Josep M; Bonal, Raul; Sánchez-Humanes, Belén (Journal of Ecology, 2009)
1. Pre-dispersal seed predation (PSP) often occurs in multi-host–predator systems (e.g. several plant species exposed to a common array of granivorous insects). However, whether the interaction among seed phenology, seed size and predator size accounts for interspecific differences in PSP remains elusive. 2. We studied PSP in a mixed-oak forest with two oaks (the larger-seeded Quercus humilis and the smaller-seeded Q. ilex), both depredated by two acorn weevils (the smaller Curculio glandium and the larger C. elephas). We intensively monitored acorn production and infestation phenology and we identified the weevil species depredating acorns by means of DNA taxonomy. 3. The minimum acorn size required for infestation was lower for C. glandium than for C. elephas, in accordance with their different body sizes. This resulted in an earlier infestation phenology in C. glandium and the ability of this species to infest both smaller and larger acorns. Above a minimum acorn size threshold, no selection for larger acorns by weevils was observed. 4. Initial acorn crop size was similar in the two oaks. Nonetheless, the earlier acorn phenology and the production of larger acorns in Q. humilis favoured the earlier infestation by C. glandium and the predation by both small and large weevils. Smaller acorns of Q. ilex almost excluded infestation by the larger C. elephas. 5. Although larger acorns of Q. humilis could better survive infestation (preserve the embryo), higher PSP in this species finally resulted in a lower mature acorn crop size than in Q. ilex. 6. Synthesis. In a multi-host–predator system, smaller-seeded species may benefit from a reduced PSP because they exclude larger granivorous insects, but also by means of a ‘free-rider effect’, if larger-seeded heterospecifics earlier reach a critical size to be depredated. These results also highlight the benefits of a small body size in granivorous insects to depredate seeds earlier and to forage on a wider range of seed sizes. Whether the advantage of ‘being small’ in this antagonistic plant–animal interaction is offset by other processes, or whether it results in a pressure towards seed and insect size reduction, deserves further attention.
Keywords: Curculio elephas; Curculio glandium; Mediterranean oak forests; multi-host–predator system; Quercus humilis; Quercus ilex; seed ecology; seed satiation; species coexistence

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size

Satiation of predispersal seed predators: the importance of considering both plant and seed levels - Bonal, Raul; Muñoz, Alberto; Díaz, Mario (Evolutionary Ecology, 2006)
Plants can reduce the ﬁtness costs of granivory by satiating seed predators. The most common satiation mechanism is the production of large crops, which ensures that a proportion of the seeds survive predation. Nevertheless, satiation of small granivores at the seed level may also exist. Larger seeds would satiate more efﬁciently, enhancing the probability of seed survival after having been attacked. However, a larger seed size could compromise the efﬁciency of satiation by means of large crops if there were a negative relationship between seed size and the number of seeds produced by an individual plant. We analyze both types of satiation in the interaction between the holm oak Quercus ilex and the chestnut weevil Curculio elephas. Both crop size and acorn size differed strongly in a sample of 32 trees. Larger crop sizes satiated weevils, and higher proportions of the seeds were not attacked as crop size increased. Larger seeds also satiated weevil larvae, as a larger acorn size increased the likelihood of embryo survival. Seedling size was strongly related to acorn size and was reduced by weevil attack, but seedlings coming from large weeviled acorns were still larger. The number and the size of the acorns produced by individual trees were negatively related. Larger proportions of the crop were infested in oaks producing less numerous crops of larger acorns. However, contrary to expectations, these trees did not satiate more effectively at the seed level either. Effective satiation by larger acorns was precluded by larger multi-infestation rates associated to smaller seed crops, in such a way that the proportion of attacked seeds that survived did not vary among trees with different acorn sizes. These results highlight the need of considering satiation by means of large crops and large seeds in studies of predispersal seed predation. Long-term monitoring on individual oaks will help to assess whether there is a trade-off between the number and the size of the acorns and, if it existed, how it could condition the ﬁtness consequences of both types of satiation
Keywords: Curculio; granivorous insects; Multi-infestation; Predispersal seed predation; Quercus; Satiation; Seed number; Seed size